Bis-choline tetrathiomolybdate in patients with Wilson's disease: an open-label, multicentre, phase 2 study. (December 2017) - Weiss, Karl Heinz; Askari, Frederick K; Czlonkowska, Anna; Ferenci, Peter; Bronstein, Jeff M; Bega, Danny; Ala, Aftab; Nicholl, David; Flint, Susan; Olsson, Lars; Plitz, Thomas; Bjartmar, Carl; et al.
Summary: Background: Wilson's disease is a genetic disorder in which copper accumulates in the liver, brain, and other tissues. Therapies are limited by efficacy, safety concerns, and multiple daily dosing. Bis-choline tetrathiomolybdate (WTX101) is an oral first-in-class copper-protein-binding molecule that targets hepatic intracellular copper and reduces plasma non-ceruloplasmin-bound copper (NCC) by forming tripartite complexes with albumin and increasing biliary copper excretion. We aimed to assess the efficacy and safety of WTX101 in the initial or early treatment of patients with Wilson's disease. Methods: We did this open-label, phase 2 study at 11 hospitals in the USA and Europe. We enrolled patients (≥18 years) with Wilson's disease who were untreated or had received no more than 24 months of treatment with chelators or zinc, had a Leipzig score of 4 or more, and had NCC concentrations above the lower limit of the normal reference range (≥0·8 μmol/L). Eligible patients received WTX101 monotherapy at a starting dose of 15–60 mg/day on the basis of baseline NCC concentrations for the first 4–8 weeks, with response-guided individualised dosing for the remaining weeks up to week 24. Investigators, other hospital personnel, and patients were aware of the identity of the treatment. The primary endpoint was change in baseline NCC concentrations corrected for copper in tetrathiomolybdate-copper-albumin complexes (NCCcorrected ) at 24 weeks, with treatment success defined as achievement or maintenance of normalised NCCcorrected (≤2·3 μmol/L [upper limit of normal]) or achievement of at least a 25% reduction in NCCcorrected from baseline at 24 weeks. This study is registered withClinicalTrials.gov, numberNCT02273596 . Findings: Between Nov 24, 2014, and April 27, 2016, 28 patients were enrolled and received WTX101; 22 (79%) patients completed the study up to week 24. At 24 weeks, 20 (71%, 95% CI 51·3–86·8; p<0·0001) of 28 patients met the criteria for treatment success: 16 (57%) treated with WTX101 either achieved or maintained normalised NCCcorrected concentrations and 4 (14%) had at least a 25% reduction from baseline NCCcorrected . Mean NCCcorrected was reduced by 72% from baseline to week 24 (least squares mean difference −2·4 μmol/L [SE 0·4], 95% CI −3·2 to −1·6; p<0·0001). No cases of paradoxical drug-related neurological worsening were recorded. Liver function was stable in all patients, although reversible increased concentrations of asymptomatic alanine or aspartate aminotransferase, or γ-glutamyltransferase, without increased bilirubin, occurred in 11 (39%) of 28 patients who received at least 30 mg/day. 11 serious adverse events were reported in seven (25%) patients and included psychiatric disorders (six events in four patients), gait disturbance (one event), elevated liver aminotransferases (two events in two patients, one with agranulocytosis), and decline in neurological functioning (one event, likely due to natural disease progression although causality could not be ruled out). The seven serious adverse events categorised as psychiatric disorders and as gait disturbance were assessed as unlikely to be related to the study drug, whereas the remaining four events were possibly or probably related. Interpretation: Our findings indicate that WTX101 might be a promising new therapeutic approach for Wilson's disease, with a unique mode of action. In view of its once-daily dose and favourable safety profile, WTX101 could improve the treatment of patients with this debilitating condition. Funding: Wilson Therapeutics AB.